2001
DOI: 10.1111/j.1572-0241.2001.03607.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum amylase and lipase activities in normal pregnancy: a prospective case-control study

Abstract: An increase in serum amylase and lipase activities during pregnancy should be taken into account, as in nonpregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…The level of serum lipase was lesser when it was compared to control. A study conducted by Karsenti et al 15 observed that the serum lipase activity was decreased during first trimester and mechanism behind this is not known. In this study the level of serum amylase in nonpregnant women (69.66 ± 16.45 U/L) when compared to the case of hyperemesis gravidarum (76.40 ± 33.86U/L) was also not statistically significant (p=0.210) as shown in Table 2.…”
Section: Discussionmentioning
confidence: 98%
“…The level of serum lipase was lesser when it was compared to control. A study conducted by Karsenti et al 15 observed that the serum lipase activity was decreased during first trimester and mechanism behind this is not known. In this study the level of serum amylase in nonpregnant women (69.66 ± 16.45 U/L) when compared to the case of hyperemesis gravidarum (76.40 ± 33.86U/L) was also not statistically significant (p=0.210) as shown in Table 2.…”
Section: Discussionmentioning
confidence: 98%
“…Serum amylase activity does not change significantly during pregnancy. 65,72,77 Serum lipase activity is significantly lower in first trimester but not in second and third trimesters compared with nonpregnant women. 77 Important causes of acutely elevated transaminases in pregnancy include PET/HELLP, drug reactions, AFLP, viral and autoimmune hepatitis, sepsis, hyperemesis gravidarum and intrahepatic cholestasis of pregnancy (ICP).…”
Section: Liver Testsmentioning
confidence: 98%
“…Serum amylase activity does not change significantly during pregnancy . Serum lipase activity is significantly lower in first trimester but not in second and third trimesters compared with non‐pregnant women …”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…La lipasa tiene la ventaja de ser más específica y de permanecer elevada por más tiempo que la amilasa (Working Group IAP/APA, 2013; Sarr, 2013). Se ha reportado que en embarazos normales los niveles de estas enzimas permanecen normales o muy levemente elevados (Karsenti et al, 2001;Larsson et al, 2008). (Garel et al, 1998;Uribe et al, 2009).…”
Section: Consideraciones Diagnósticas En El Embarazounclassified